2022
DOI: 10.1007/s00262-022-03253-x
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab, radiotherapy, and an immunomodulatory five-drug cocktail in pretreated patients with persistent, recurrent, or metastatic cervical or endometrial carcinoma: Results of the phase II PRIMMO study

Abstract: A phase II study (PRIMMO) of patients with pretreated persistent/recurrent/metastatic cervical or endometrial cancer is presented. Patients received an immunomodulatory five-drug cocktail (IDC) consisting of low-dose cyclophosphamide, aspirin, lansoprazole, vitamin D, and curcumin starting 2 weeks before radioimmunotherapy. Pembrolizumab was administered three-weekly from day 15 onwards; one of the tumor lesions was irradiated (8Gyx3) on days 15, 17, and 19. The primary endpoint was the objective response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The authors acknowledge the insufficient sample size and the favourable results of nivolumab alone in the metastatic HNSCC control group. Similar negative results have been reported for other carcinomas [ 16 , 17 ]. In these trials that aimed to induce the AE in patients with metastasis, SBRT was often delivered at relatively low doses, such as 24–30 Gy in three fractions.…”
Section: Discussionsupporting
confidence: 90%
“…The authors acknowledge the insufficient sample size and the favourable results of nivolumab alone in the metastatic HNSCC control group. Similar negative results have been reported for other carcinomas [ 16 , 17 ]. In these trials that aimed to induce the AE in patients with metastasis, SBRT was often delivered at relatively low doses, such as 24–30 Gy in three fractions.…”
Section: Discussionsupporting
confidence: 90%
“…A pooled analysis of the PEMBRO-RT and MDACC trials assessed metastatic NSCLC patients receiving pembrolizumab with or without radiotherapy found that patients undergoing radiation had a higher abscopal response rate (41.7% vs. 19.7%) [ 41 ]. However, other phase II clinical trials that evaluated the combination of SABR and immunotherapy have failed to demonstrate the abscopal effect in a variety of histologies [ 42 ] including renal cell carcinoma [ 43 ], head and neck [ 44 ], NSCLC [ 45 ], cervical/endometrial [ 46 ] and colorectal cancer [ 47 ]. This includes the ongoing CHEERS trial, a multicenter phase II trial randomizing locally advanced or metastatic patients to receive SABR and anti-PD-(L)1 immunotherapy or immunotherapy alone.…”
Section: Lesson #9: Don’t Count On the Abscopal Effectmentioning
confidence: 99%
“…In 2010, a Japanese case-control study including 405 patients with incidental cervical neoplasias found that cervical cancer risk was reduced by increasing vitamin D intake [26], suggesting that vitamin D plays a protective role for cervical cancer. To date, no clinical trials have been conducted that have demonstrated the expected beneficial effects of vitamin D 3 , 25OHD 3 or calcitriol per se on women with invasive cervical cancer, but they have been developed in combination with other antineoplastic drugs, including a phase II study (NCT03192059) that enrolled cervical or endometrial cancer patients, who received a cocktail of low-dose of cyclophosphamide, aspirin, lansoprazole, vitamin D, and curcumin starting 2 weeks before radioimmunotherapy; the antitumor activity was modest but durable, and the toxicity was acceptable but not negligible [81]. A limited number of clinical trials have studied the effect of long-term vitamin D supplementation on precancerous lesions of the cervix.…”
Section: The Vitamin D Endocrine System In Cervical Cancer: Clinical ...mentioning
confidence: 99%